A Netnographic Reception Analysis of Main News Bulletins - Türker Söğütlüler (Yeni Medya)
Ethnography, one of the long-established methods of social sciences, has been frequently used especially by the fields of anthropology and sociology, and has come to the fore in the research of practices related to the social. The interactive structure of the internet with Web 2.0 has brought the idea of adapting the ethnography method to digital fields to the agenda. The foundations of a new method called Netnography, which focuses on examining the behaviour of virtual communities, have been laid and communication sciences have taken a leading role in its use. Researchers of the British Cultural Studies Tradition introduced the reception method to the literature and proposed a model called encoding-decoding. Contrary to the American Behaviourist Approach, the researchers stated that the texts presented by the mass media are not met with absolute acceptance by the society and argued that individuals construct a new meaning by filtering the messages presented through their own filters. In this study, by using these two methods together, the netnographic reception patterns of Ekşi Sözlük users regarding Atv Main News and Fox Main News bulletins were investigated. The 703 entries under the titles of the news bulletins in Ekşi Sözlük were analysed and categorised as dominant, negotiative and oppositional reading styles. Frequency distributions were generated using IBM SPSS Statistics 22.0 programme. Netnography method and reception methods were found to be suitable for use together; it was concluded that the reception styles of the viewers turned from dominant to negotiative and oppositional due to the departure of the popular presenter from the programme, the change in the ideological orientation of the programme, the non-compliance with the principle of impartiality, and the echo chamber effect.